Parties and party systems : a framework for analysis - Sartori, Giovanni, 1924-; European Consortium for Political Research (Colchester : ECPR, 1976)
In this broad-ranging volume Sartori outlines a comprehensive and authoritative approach to the classification of party systems. He also offers an extensive review of the concept and rationale of the political party, and develops a sharp critique of various spatial models of party competition.
Includes index.
Keywords: Political parties